323 Prevalence and Predictors of Inappropriate Pre-injury Antithrombotic Use in Patients Presenting with TBI. (1st April 2022) - Mashouf, Leila A.; Nieves, Amber; Matos, Jason; Yaffe, Michael; Stippler, Martina
Abstract : INTRODUCTION: A growing proportion of the US population is on antithrombotic therapy (AT), expanding most significantly within the elderly subpopulation. The intended benefits of AT are balanced by known increased bleeding risk, salient after traumatic brain injury (TBI). Inappropriate pre-injury AT (IAT) in patients presenting with TBI confers unbalanced risk of poor outcomes and has yet to be described in existing literature. METHODS: A retrospective chart review was performed on all patients with TBI and pre-injury AT who presented to our institution between January 2016 and September 2020. Demographic and clinical data was collected from the medical record. IAT status was determined through established clinical algorithms in combination with American College of Cardiology practice guidelines. Clinical predictors were determined by logistic regression. RESULTS: Of 169 included patients, 59% were male (n = 100) and mean age was 82 years. AT agents included aspirin (n = 46), clopidogrel (n = 45), coumadin (n = 77), dabigatran (n = 4), rivaroxaban (n = 17), and apixaban (n = 30). Overall surgical intervention, complication, and death rates were 7.7%, 15.4%, and 20.1%, respectively. IAT was found in 10.6% of patients overall: in 41% (n = 6) of patients with documented indication of pulmonary embolism, in 6.2% with documented indication of atrial fibrillation (AF) (n = 6), in 24% with documented indication of cardiac stents (n = 5). Age was a significant negative predictor of IAT use in patients with documented indication of AF (p=0.009). Gender, race, and AT agent were not significant predictors. CONCLUSION: 1 in 10 patients presenting with TBI were found to be on IAT. Our study is the first to describe this population and warrants investigation into workflow interventions that initiate verification or deprescription of AT by neurosurgeons treating TBI and outpatient prescribers.